2020
DOI: 10.1016/j.scs.2020.102259
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria roof sorting for the integration of photovoltaic systems in urban environments

Abstract: Authors would like to thanks the program INTERREG V Suisse-France for providing financial support to conduct this study in the framework of the project G2 Solar which aims at extending the solar cadaster to the Greater Geneva and intensify energy solar production at this level. We greatly acknowledge R. Giraudon at Urban Solar Energy, and B. Benchenafi at Reservoir Sun, for their helpful discussion and their expertise. We finally thank Manon Turban for her proofreading of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…The main characteristics, which affect the use of the roof for the installation of PV panels, are the roof shape, architectural characteristics, morphological context, building codes, and regulations. According to the literature review [18][19][20][21][22][23], the criteria identified in this work to evaluate the roof suitability for the installation of PV panels are:…”
Section: Input Data Processingmentioning
confidence: 99%
“…The main characteristics, which affect the use of the roof for the installation of PV panels, are the roof shape, architectural characteristics, morphological context, building codes, and regulations. According to the literature review [18][19][20][21][22][23], the criteria identified in this work to evaluate the roof suitability for the installation of PV panels are:…”
Section: Input Data Processingmentioning
confidence: 99%
“…However, research teams from Geneva (Switzerland) [61] and Valencia (Spain) [62], almost in parallel, proposed their methods for including shading in the calculations. In addition, it was considered important to classify roofs according to their suitability for the installation of photovoltaic systems [34]. The study area was once again Geneva.…”
Section: Solar Cadastrementioning
confidence: 99%
“…Finally, a decision tree is used to find the optimal match between RE generation and electricity demand of the municipality. Regarding pure spatial assessment at urban scale, with no temporal dimension, Thebault et al [6] have developed a multicriteria sorting tool in order to assess the suitability of a roof to host solar PV systems. The authors combine GIS with the ELECTRE TRI methodology according to predefined weighted criteria such as superstructure constraints, economic feasibility or yearly solar irradiation in order to sort roofs of a given area with respect to its degree of suitability.…”
Section: Re Planning and Spatiotemporal Modeling: A Literature Reviewmentioning
confidence: 99%